David G. Hunter, Paul van Geest, Bert Jan Lietaert Peerbolte (Eds.), Brill Encyclopedia of Early Christianity. Authors, Texts, and Ideas. Leiden: Brill, 2024 - Giudice, Hernán (2024)
Fil: Giudice, Hernán, investigador independiente; Argentina